Current clinical management of patients with glioblastoma. Issue 6 (4th September 2019) - Lowe, Stephen; Bhat, Krishna P.; Olar, Adriana
Abstract: Background: Glioblastoma (GB) is the most aggressive primary brain tumor, historically resistant to treatment, and with overall fatal outcome. Recent findings: Recently, several molecular subgroups and rare genetic alterations have been described in GB. In this review article, we will describe the current clinical management of patients with GB in the United States, discuss selected next‐generation molecular‐targeted therapies in GB, and present ongoing clinical trials for patients with GB. This review is intended for clinical and preclinical researchers who conduct work on GB and would like to understand more about the current standard of treatment of GB patients, historical perspectives, current challenges, and ongoing and upcoming clinical trials. Conclusions: GB is an extremely complex disease, and despite recent progress and advanced therapeutic strategies, the overall patient's prognosis remains dismal. Innovative strategies and integrative ways of approach to disease are urgently needed.